Influence of advanced shoe technology on the top 100 annual performances in men`s marathon from 2015 to 2019 - Rodrigo-Carranza, V.; González-Mohíno, F.; Santos del Cerro, J.; Santos-Concejero, J.; González-Ravé, J. M- (Scientific Reports, 2021)
The NIKE Vaporfly shoe was introduced in May 2017 as part of the original #Breaking2 Project (an event aimed to run the first marathon under 2 h). This new advanced shoe technology (NAST) changed the footwear design conception. The aim of this study was (i) to analyse the effect of NAST in men`s marathon performance, (ii) to analyse whether the changes in the environmental constraints (temperature and wind) and orography of the marathons, age and birthplace of the runners has changed from 2015 to 2019 and (iii) to analyse the impact of NAST on the historical 50 best performances. Data from top-100 men's marathon performances were collected in that timeframe. The shoes used by the athletes were identified (in 91.8% of the cases) by publicly available photographs. External and environmental conditions of each marathon and age and birthplace of the runners were also analysed. Marathon performances improved from 2017 onwards between 0.75 and 1.50% compared to 2015 and 2016 (p < 0.05). In addition, the improvement was greater in the upper deciles than in the lower ones (p < 0.001). Runners wearing NAST ran ~ 1% faster in marathon compared to runners that did not use it (p < 0.001). When conducting an individual analysis of athletes who ran with and without NAST, 72.5% of the athletes who completed a marathon wearing NAST improved their performance by 0.68% (p < 0.01). External and environmental conditions, age or birthplace of runners seems not to have influenced this performance improvement. NAST has had a clear impact on marathon performance unchanged in the environmental constraints (temperature and wind), orography, age, and birthplace of the runners but with differences between venues.